Gene trapping reveals a new transcriptionally active genome element: The chromosome‐specific clustered trap region. (30th August 2021) - Takeda, Iyo; Araki, Masatake; Ishiguro, Kei‐ichiro; Ohga, Toshinori; Takada, Kouki; Yamaguchi, Yusuke; Hashimoto, Koichi; Kai, Takuma; Nakagata, Naomi; Imasaka, Mai; Yoshinobu, Kumiko; Araki, Kimi
Abstract: Nearly half of the human genome consists of repetitive sequences such as long interspersed nuclear elements. The relationship between these repeating sequences and diseases has remained unclear. Gene trapping is a useful technique for disrupting a gene and expressing a reporter gene by using the promoter activity of the gene. The analysis of trapped genes revealed a new genome element—the chromosome‐specific clustered trap (CSCT) region. For any examined sequence within this region, an equivalent was found using the BLAT of the University of California, Santa Cruz (UCSC) Genome Browser. CSCT13 mapped to chromosome 13 and contained only three genes. To elucidate its in vivo function, the whole CSCT13 region (1.6 Mbp) was deleted using the CRISPR/Cas9 system in mouse embryonic stem cells, and subsequently, a CSCT13 knockout mouse line was established. The rate of homozygotes was significantly lower than expected according to Mendel's laws. In addition, the number of offspring obtained by mating homozygotes was significantly smaller than that obtained by crossing controls. Furthermore, CSCT13 might have an effect on meiotic homologous recombination. This study identifies a transcriptionally active CSCT with an important role in mouse development. Abstract : The analysis of trapped genes showed a new genome element—the chromosome‐specific clustered trap (CSCT) region. This study identifies a transcriptionally active CSCT with an important role in mouse development.